# CONTINUOUS MAPS1

Philip Lester P. Benjamin Mindanao State University Iligan Institute of technology Tibanga, Iligan city plbenj@yahoo.com

THEOREM 8.3
Let X ,Y be a topological space and f : X → Y . The following are equivalent:

1. f is continuous. 2. Inverse image of each closed set in Y is closed in X . 3. Inverse image of each member of a subbasis(basis) for Y is open in X . 4. ∀x ∈ X and ∀nbd W (f (x)) in Y , ∃nbd V (x) in X s.t f (V (x)) ⊆ W (f (x)). 5. f (A) ⊆ f (A) ∀A ⊆ X 6. f −1 (B ) ⊆ f −1 (B ) ∀B ⊆ Y Proof: (1) ⇒ (2) : Let f be continuous and let E be any closed set in Y . Then Y \E is open in Y . By continuity of f , f −1 (Y \E ) = X − f −1 (E ) is open in X . Thus, f −1 (E ) is closed in X . (2) ⇒ (1) : Let U be any open set in Y . Then Y \U is closed in Y . By assumption, f (Y − U ) = X − f −1 (U ) is closed in X . Thus, f −1 (U ) is open in X . Hence, f is continuous. (1) ⇒ (3) : Let B be any subbasic(basic) element of Y . Then clearly, B is open in Y . By continuity of f , f −1 (B ) is open in X .
−1

(3) ⇒ (1) : Let O be any open set in Y . Then by the deﬁnition of a subbasis or basis, O=
B ∈B
1

B

or O =
S ∈B

S , where B is a subbasis or basis of Y .

This is a report on general topology, date: January 11, 2013.

(1) ⇒ (4) : Let x ∈ X and let W (f (x)) be any nbd of f (x) in Y . f −1 (F ) ⊆ f −1 (F ).t f (V (f −1 (b))) ⊆ W (b).L Benjamin B f −1 (B ) B ∈B = is open in X since f −1 (B ) is open in X by (3). Hence. f (V (x)) ⊆ W (f (x)). Clearly. f −1 (F ) ⊆ f −1 (F ). ∃nbd V (x) s. Since b ∈ f (A).2 Now. f (A) ⊆ f (A). Thus. f (A) = f (f −1 (B )) ⊆ f (A) = f (f −1 (B )) = B This implies that f (f −1 (B )) ⊆ B . f −1 (O) = f −1 B ∈B P. Therefore. By deﬁnition of a nbd. ∅ = V (f −1 (b)) ∩ A. (5) ⇒ (6) : Let B ⊆ Y and let f −1 (B ) = A. CLAIM: b ∈ f (A) Let W (b) be any nbd of b in Y . By continuity of f . By (5). f −1 (F ) is closed in X . ∃nbd V (f −1 (b)) s. f −1 (F ) ⊆ f −1 (F ) = f −1 (F ). Then by hypothesis. This completes the proof. f −1 (W (f (x))) is open in X . Hence. . (4) ⇒ (5) : Let A ⊆ X and let b ∈ f (A). Hence. f −1 (F ) = f −1 (F ). Then by (6). W (f (x)) is open in Y . f −1 (b) ∈ A. or f −1 (O) = f −1 S ∈B S f −1 (S ) = S ∈B is open in X since f −1 (S ) is open in X by (3). It implies that ∅ = f (V (f −1 (b)) ∩ A) = f (V (f −1 (b))) ∩ f (A) ⊆ W (b) ∩ f (A) This implies that ∅ = W (b) ∩ f (A) so that b ∈ f (A).t V (x) ⊆ f −1 (W (f (x))). Since −1 −1 x ∈ f (W (f (x))) and f (W (f (x))) is open in X . f −1 (B ) ⊆ f −1 (B ). Since V (f −1 (b)) is a nbd of f −1 (b) ∈ A. Hence. (6) ⇒ (2) : Let F be any closed set in Y .